Green syntheses of silver nanoparticle decorated reduced graphene oxide using l-methionine as a reducing and stabilizing agent for enhanced catalytic hydrogenation of 4-nitrophenol and antibacterial activity. Issue 67 (28th November 2019) - Belachew, Neway; Meshesha, Desta Shumuye; Basavaiah, Keloth
Abstract : Herein, we have reported a facile and green synthesis approach of Ag NP decorated reduced graphene oxide (RGO) through an in situ self-assembly method in the presence of l -methionine (l -Met) as reducing and stabilizing agent. Abstract : Herein, we have reported a facile and green synthesis approach of Ag NP decorated reduced graphene oxide (RGO) through an in situ self-assembly method in the presence of l -methionine (l -Met) as reducing and stabilizing agent. The electronic properties, crystal structure, and morphology of the as-synthesized RGO–Ag nanocomposite were investigated by UV-Visible (UV-Vis) spectroscopy, Fourier transform-infrared (FTIR), X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) techniques. UV-Vis and FTIR show the effective reduction of GO and the formation of Ag NPs using l -Met. FESEM, TEM, and XRD analysis show the successful impregnation of Ag NPs into RGO with a 23 nm average crystallite size. The RGO–Ag nanocomposite with NaBH4 shows a fast-catalytic reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AMP). The enhanced catalytic activity of RGO–Ag nanocomposites can be attributed to the synergistic effect of improved adsorption capacity and the absence of agglomeration of Ag nanoparticles. Moreover, RGO–Ag showed strong antibacterial activity against B. subtilis and E. coli .